Partisipasi Pedagang dalam Pengelolaan Sampah Pasar Sentral Laino Kabupaten Muna - Wa Ode Puput; Abdul Manan; Safril Kasim; La Ode Midi; La Ode Siwi; Asramid Yasin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The purpose of this research is to find out the Participation of Traders in the Waste Management of the Laino Central Market of Muna Regency City. This research uses several methods of Porposive Sampling techniques. The slovin formula is used to determine the number of samples that will be studied, and qualitative descriptive analysis is used to analyze the market waste management system, the behavior of traders carried out by collecting data through observation, interviews, documentation. Based on the results of this study, it can be concluded that the Participation of Traders in the Waste Management of the Laino Central Market of Muna Regency with a medium participation criterion of 61,44 %. This can be seen from the articipation of traders such as providing garbage containers at the sales location, collecting waste directly to the temporary disposal site, easy to reach the temporary disposal location, on time in paying dues, cleaning garbage before and after trading, approving people who dispose of garbage correctly. While the rest with a low criterion of 38.55% shows the lack of Participation of Traders in Market Waste Management in terms of attending meetings to discuss hygiene issues, and a joint evaluation of the cleanliness of the Market Environment.